RESPON PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L. var Lembah Palu) TERHADAP KONSENTRASI PUPUK ORGANIK CAIR - Alfonsus Yudhanto Sara; Selvie Tumbelaka; Rinny Mamarimbing (COCOS, 2019)
ABSTRACT Shallots (Allium ascalonicum L.) is one of the main vegetable commoditis in Indonesia and has many benefits. Shallots are included in the group of spices needed by household consumers as seasonings for cooking and raw materials for the food industry and traditional medicinal ingredients. Based on data from the National Nutrient Database shallots contain carbohydrates, sugars, fatty acids, proteins and other minerals needed by the human body (Waluyo dan Sinaga, 2015). The objective of research was to study the the growh and yield response of shallot (Allium ascalonicum L. var Lembah palu) on liquid organic fertilizer concentration. The research was conducted at field of Agriculture Faculty University of Sam Ratulangi in Manado from July to October 2019. This experiment was designed using a randomized block design with five treatments and five replications. The treatment was concentrations of liquid organic fertilizer which consist of five levels, ahat are ; Po = control, P1 = 1 ml/l water, P2 = 3 ml/l water, P3 = 5 ml/l water, and P4 = 7 ml/l water. Parameters include observations of plant height, number of leaves, number of tubers, fresh weight and day weight of tubers. The results of experiment showed that application of liquid organic fertilizer have an effect to the growth and yield of shallots. In the treatment of 5 ml / l concentration of water produced the highest average production with the number of tubers perump (11 tubers), fresh weight (57,298 grams), and dry weight (50,924 grams). Keywords: Shallot, Concentration, POC, Growth, Yield